Bis(β-lactosyl)-[60]fullerene as novel class of glycolipids useful for the detection and the decontamination of biological toxins of the Ricinus communis family - Hirofumi Dohi; Takeru Kanazawa; Akihiro Saito; Keita Sato; Hirotaka Uzawa; Yasuo Seto; Yoshihiro Nishida (Beilstein Journal of Organic Chemistry, 2014)
Glycosyl-[60]fullerenes were first used as decontaminants against ricin, a lactose recognition proteotoxin in the Ricinus communis family. A fullerene glycoconjugate carrying two lactose units was synthesized by a [3 + 2] cycloaddition reaction between C60 and the azide group in 6-azidohexyl β-lactoside per-O-acetate. A colloidal aqueous solution with brown color was prepared from deprotected bis(lactosyl)-C60 and was found stable for more than 6 months keeping its red color. Upon mixing with an aqueous solution of Ricinus communis agglutinin (RCA120), the colloidal solution soon caused precipitations, while becoming colorless and transparent. In contrast, a solution of concanavalin A (Con A) caused no apparent change, indicating that the precipitation was caused specifically by carbohydrate–protein interactions. This notable phenomenon was quantified by means of sodium dodecyl sulfate polyacrylamide gel electrophoresis (SDS-PAGE), and the results were discussed in terms of detection and decontamination of the deadly biological toxin in the Ricinus communis family.